Safety monitoring of cytostatic handling - Hilda M. Rodríguez Montero; Elizabeth Reyes Reyes; Tania M. Escalante Leyva; Raidel Correa Aguila; Antonio Torres Valle; Elizabeth B. Cuétara-Lug (GarVal Editorial Ltda., 2018)
Context: The Institute of Oncology and Radiobiology (INOR) is the leading institution for the diagnosis, treatment and follow up of cancer in Cuba. Cancer treatment is mainly by three methods: surgery, radiotherapy and chemotherapy. Pharmacological treatments involve the use of dangerous substances such as cytostatics, the handling of which threat the health of the occupationally exposed staff. Aims: To evaluate a biomarker of genotoxicity indicative of DNA damage in the biomonitoring of occupational risks associated with the administration of antineoplastic drugs to hospitalized patients. Methods: The determination of the frequency of micronuclei, in cells of the exfoliated oral mucosa was determined (Micronucleus test) in subjects who administer cytostatic drugs at the institute and a control group formed by administrative personal. Results: Present results evidenced that all exposed subjects possess the same DNA damage that non-exposed-ones. Such results are in concordance with the proper use of primary protection barriers and the adhesion to normalized operational procedures. Conclusions: The frequency of micronuclei is a useful biomarker for assessing DNA damage associated with the administration of antineoplastic drugs. The risk perception analysis (RISKPERCEP) in occupationally exposed subjects complements the occupational safety monitoring.